VALUE PREFERENCES IN RELATION TO PREJUDICE TOWARD OUTGROUPS - Vera, Juan José; Martínez, Mª del Carmen (Anales de Psicología / Annals of Psychology)
This article analizes the relationship between value types, formulated in the Theory of Universal Content and Structure of Values, and the prejudice toward different outgroups (gipsy, mogrebian and south-american people). It was applicated the model developed by Schwartz (1992) and a survey about prejudices (Martínez & Vera, 1994) to a sample of 165 undegraduate students.The structure proposed by Schwartz is obtained in the students' empirical mapping of values. Moreover, the differences between prejudiced and nonprejudiced people are related to value orientations as achievement, power and universalism.